1993
DOI: 10.1177/000348949310201007
|View full text |Cite
|
Sign up to set email alerts
|

Air Pulse Quantification of Supraglottic and Pharyngeal Sensation: A New Technique

Abstract: There are no published studies evaluating the sensory capacity of the region innervated by the superior laryngeal nerve. A normal sensory capacity is important in this area, since hypesthesia or anesthesia of the pharynx and supraglottic larynx may result in dysphagia and aspiration. This often occurs after stroke or after ablative surgery of the pharynx and larynx. Evaluating the efficacy of restorative procedures for supraglottic and pharyngeal sensation is dependent on defining and quantifying the sensory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 9 publications
2
124
0
2
Order By: Relevance
“…It has been reported that long-term tracheotomy results in diminished and eventual loss of abductor (posterior cricoarytenoid muscle) activity [22] and a weakened, poorly coordinated laryngeal closure (thyroarytenoid muscle) response [35]. The laryngeal closure reflex in different populations, including patients with tracheotomy and ventilator dependency, needs to be investigated with the FEES with a sensory testing technique [36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that long-term tracheotomy results in diminished and eventual loss of abductor (posterior cricoarytenoid muscle) activity [22] and a weakened, poorly coordinated laryngeal closure (thyroarytenoid muscle) response [35]. The laryngeal closure reflex in different populations, including patients with tracheotomy and ventilator dependency, needs to be investigated with the FEES with a sensory testing technique [36].…”
Section: Discussionmentioning
confidence: 99%
“…This is at odds with the well-documented observations that the majority of swallow-related measures among older people reveal slower and less ecient swallowing [2,31±33]. These include increased stagetransition duration, pharyngeal transit duration, duration to UES opening, and total swallowing duration [2,31,33]; and higher sensory thresholds in the pyriform sinus [32]. The reasons for our unexpected ®nding are not clear; however, it may be related to the relative good health and younger age of our subjects compared with those of previous studies (®ve of the seven were under the age of 70).…”
Section: Age and Gender Findingsmentioning
confidence: 99%
“…Each method used air pulse stimulation of pyriform mucosa and aryepiglottic folds (the region innervated by the superior laryngeal nerve [SLN]). One method, psychophysical testing, has been described previously [12,17,18]. The second method, also previously described [13], was to elicit the laryngeal adductor reflex (LAR) as a measure of determining LP sensory thresholds.…”
Section: Feesst Protocolmentioning
confidence: 99%